Georgia - Debt Management Performance Assessment (DeMPA) - World Bank (Washington, DC, 2022)
The DeMPA is a methodology for assessing public debt management performance based on a comprehensive set of indicators spanning the full range of governmental debt management functions. It is adapted from the Public Expenditure and Financial Accountability (PEFA) framework. The DeMPA tool presents 14 performance indicators along with a scoring methodology. The DeMPA tool is complemented by a guide that provides supplemental information on using the indicators.